2018
DOI: 10.1001/jama.2018.8931
|View full text |Cite
|
Sign up to set email alerts
|

Association of Digital Media Use With Subsequent Symptoms of Attention-Deficit/Hyperactivity Disorder Among Adolescents

Abstract: IMPORTANCE Modern digital platforms are easily accessible and intensely stimulating; it is unknown whether frequent use of digital media may be associated with symptoms of attention-deficit/hyperactivity disorder (ADHD).OBJECTIVE To determine whether the frequency of using digital media among 15-and 16-year-olds without significant ADHD symptoms is associated with subsequent occurrence of ADHD symptoms during a 24-month follow-up.DESIGN, SETTING, AND PARTICIPANTS Longitudinal cohort of students in 10 Los Angel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
123
1
10

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 203 publications
(152 citation statements)
references
References 29 publications
6
123
1
10
Order By: Relevance
“…Selanjutnya, hasil penelitian menunjukkan bahwa sebagian besar anak yang memiliki kebiasaan bermain gadget lebih dari 1 jam setiap hari mengalami degradasi perkembangan sosial dengan aktivitas gadget yang tinggi akan menjadi apatis terhadap lingkungan, tingkat agresif juga akan meningkat (Ra et al, 2018).…”
Section: Hasil Dan Pembahasanunclassified
“…Selanjutnya, hasil penelitian menunjukkan bahwa sebagian besar anak yang memiliki kebiasaan bermain gadget lebih dari 1 jam setiap hari mengalami degradasi perkembangan sosial dengan aktivitas gadget yang tinggi akan menjadi apatis terhadap lingkungan, tingkat agresif juga akan meningkat (Ra et al, 2018).…”
Section: Hasil Dan Pembahasanunclassified
“…The association between watching videos and symptoms of hyperactivity/inattention might be explained by the fast pace of online videos. Fast-paced and highly stimulating media might increase general arousal and favor an attentional style of scanning and shifting, which may hinder sustained attention and impulse control [36].…”
Section: Associations Between Media Usage and Behavioral Strengths Anmentioning
confidence: 99%
“…Whereas the media activities gaming, social networking, and watching TV/videos and their associations with health and academic performance have been investigated in several studies, other media activities such as searching for information/doing homework or traditional ways of communication (e.g., telephone calling, mailing) are understudied. Furthermore, studies exploring different -academic as well as entertaining -media activities in the same study are rare [36,37]. A very recent study showed that the use of social media for the purpose of searching for information was not associated with negative mental health outcomes, whereas social media use for other purposes was [37].…”
Section: Introductionmentioning
confidence: 99%
“…However, the exact cause of ADHD is not clear; a number of factors can contribute to the development of ADHD, such as genetics, smoking, alcohol abuse, or drug use during pregnancy; exposure to environmental toxins during pregnancy, exposure to environmental toxins during growth and development, low birth weight, and brain injuries are associated with ADHD development. A recent study has indicated that there is a modest association between higher frequency of digital media use and the development of ADHD symptoms; however, further research is required to determine whether this association is causal [8]. Executive function disorder is implicated inmost symptoms of ADHD and is involved in the frontal-subcortical circuits of the brain [9].…”
Section: Introductionmentioning
confidence: 99%